2013
DOI: 10.1021/jp407080q
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mechanism of Thermal Chemical Processes in the Crystals of YAF Tripeptides by Means of Mass Spectrometry and Solid State NMR

Abstract: Thermal reactions in two Tyr-Ala-Phe (YAF) tripeptide crystals with different molecular packing (monoclinic and hexagonal), distinct stereochemistry of central amino acid (D or L alanine) and specific arrangement of molecules in the crystal lattice (head-to-tail) were investigated. Samples were heated up to 180 °C, while the melting point for YAF crystals is above the 220 °C. Below the melting temperature, in both cases the chemical reactions leading to formation of cyclic dipeptides (YA diketopiperazine) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Upon evaporation of 1 at varying source temperatures up to T = 595 K, only molecular fragments were detected, both in EI‐QMS and VUV‐TOF‐MS. Three major fragments were observed that were tentatively assigned to the loss of the C‐terminal alanine (H 2 N‐CH(CH 3 )‐COOH) possibly resulting from thermal diketopiperazine formation (C 14 H 15 N 3 O 2 , 257 amu) as well as two common tryptophan fragments which were observed in all following mass spectra: the indole cation (C 8 H 6 N + , 116 amu) and the skatole cation (C 9 H 8 N + , 130 amu).…”
Section: Resultsmentioning
confidence: 99%
“…Upon evaporation of 1 at varying source temperatures up to T = 595 K, only molecular fragments were detected, both in EI‐QMS and VUV‐TOF‐MS. Three major fragments were observed that were tentatively assigned to the loss of the C‐terminal alanine (H 2 N‐CH(CH 3 )‐COOH) possibly resulting from thermal diketopiperazine formation (C 14 H 15 N 3 O 2 , 257 amu) as well as two common tryptophan fragments which were observed in all following mass spectra: the indole cation (C 8 H 6 N + , 116 amu) and the skatole cation (C 9 H 8 N + , 130 amu).…”
Section: Resultsmentioning
confidence: 99%